Sistem Pengeringan Buah Kopi Robusta Gombengsari Dengan Metode Hot Air Drying Berbasis IoT - Aryo Pamungkas; Charis Fathul Hadi; Widhi Winata Sakti (Journal of Educational Engineering and Environment, 2026)
This study discusses a hot air drying system for Robusta coffee cherries from Gombengsari, addressing issues that disrupt traditional sun-drying processes, such as unpredictable rainfall, vulnerability to pests, and overnight storage that causes reabsorption of moisture in the dried coffee.An experimental method was employed to determine the optimal drying temperature for coffee cherries that preserves their characteristics and flavor profile. Comparative results from the hot air drying system for Robusta coffee cherries showed moisture content reductions of 25.2%, 30.27%, 37.37%, 25.10%, 30%, and 37%. The application of hot air drying influenced the final weight, moisture content levels, and average error rate of 1%. Drying was conducted over 5 hours with initial coffee weights of 300g and 500g, at temperatures starting from 45°C. For 300g batches: 45°C yielded 25.2% moisture content, 55°C yielded 30.27%, and 65°C yielded 37.37%. For 500g batches: 45°C yielded 25.10% moisture content, 55°C yielded 30%, and 65°C yielded 37%. The optimal drying condition was achieved with a 300g batch at 65°C, resulting in 37.37% moisture content reduction and a final weight of 187.9 grams.